20 Databases on (Violent and Armed) Conflicts - Singh, Ishaansh (Perspectives on terrorism, 2021)
This Research Note introduces 20 databases and datasets on violent and armed conflicts. It identifies some of their key features and their background. There is one overlap with one of the databases introduced by Neil Bowie in this issue of Perspectives on Terrorism - but different aspects of the available data are highlighted when reporting on ACLED.